The Oxidation of Thiols by Flavoprotein Oxidases: a Biocatalytic Route to Reactive Thiocarbonyls1. Issue 48 (5th October 2014) - Ewing, Tom A.; Dijkman, Willem P.; Vervoort, Jacques M.; Fraaije, Marco W.; van Berkel, Willem J. H.
Abstract Flavoprotein oxidases are a diverse class of biocatalysts, most of which catalyze the oxidation of CO, CN, or CC bonds. Flavoprotein oxidases that are known to catalyze the oxidation of CS bonds are rare, being limited to enzymes that catalyze the oxidative cleavage of thioethers. Herein, we report that various flavoprotein oxidases, previously thought to solely act on alcohols, also catalyze the oxidation of thiols to thiocarbonyls. These results highlight the versatility of enzymatic catalysis and provide a potential biocatalytic route to reactive thiocarbonyl compounds, which have a variety of applications in synthetic organic chemistry.